Factors Associated With Physical Activity Levels Among Brazilian Military Law Enforcement Officers - Lan, Fan Yun; Barbosa, Welere G; Saint Martin, Daniel R F; de Melo Keene von Koenig Soares, Edgard; Christophi, Costas A.; Kales, Stefanos N.; Molina, Guilherme E.; Grossi Porto, Luiz Guilherme (My University, 2025)
Background: There is limited understanding of the factors associated with law enforcement officers' (LEOs') physical activity levels (PALs) in Latin America. This study aims to address this gap in knowledge. Methods: We analyzed data from a cross-sectional survey among military LEOs from a northern Brazilian state. An anonymous questionnaire, which assessed participants' PAL using the short version of the International Physical Activity Questionnaires and quality of life (QoL) using the WHOQOL-BREF, was distributed to LEOs. We examined factors associated with PAL with the use of multiple linear regression models. Results: There were a total of 418 participants (38.6± 6.6 years old, 88.3% male). After adjusting for age, sex, role, rank, education, and QoL domains, each unit increase in body mass index (BMI) and the environmental QoL domain were associated with a mean decrease of 56.2 MET-min/week and an increase of 12.8 MET-min/week in PAL, respectively (both P < 0.05). Additionally, those with a college education or higher had a mean PAL increase of 381.1 MET-min/week compared to their counterparts (P = 0.005). Conclusions: Lower BMI, higher education, and improved environmental QoL are associated with increased PAL among Brazilian military LEOs. Our findings are consistent with existing literature.
Keywords: IPAQ; Skidmore College; first responder; lifestyle; occupational health; police; quality of life